One-year cognitive and neurologic outcomes in survivors of paediatric extracorporeal cardiopulmonary resuscitation. (June 2019) - Meert, Kathleen; Slomine, Beth S.; Silverstein, Faye S.; Christensen, James; Ichord, Rebecca; Telford, Russell; Holubkov, Richard; Dean, J. Michael; Moler, Frank W.; ,
Abstract: Objective: To describe one-year cognitive and neurologic outcomes among extracorporeal cardiopulmonary resuscitation (ECPR) survivors enrolled in the Therapeutic Hypothermia after Paediatric Cardiac Arrest In-Hospital (THAPCA-IH) trial; and compare outcomes between survivors who received ECPR, later extracorporeal membrane oxygenation (ECMO), or no ECMO. Methods: All children recruited to THAPCA-IH were comatose post-arrest. Neurobehavioral function was assessed by caregivers using the Vineland Adaptive Behaviour Scales, 2nd edition (VABS-II) at pre-arrest baseline and 12 months post-arrest. Age-appropriate cognitive performance measures (Mullen Scales of Early Learning or Wechsler Abbreviated Scale of Intelligence) and neurologic examinations were obtained 12 months post-arrest. VABS-II and cognitive performance measures were transformed to standard scores (mean = 100, SD = 15) with higher scores representing better performance. Only children with broadly normal pre-arrest function (VABS-II ≥70) were included in this analysis. Results: One-year follow-up was attained for 127 survivors with pre-arrest VABS-II ≥70. Of these, 57 received ECPR, 14 received ECMO later in their course, and 56 did not receive ECMO. VABS-II assessments were completed at 12 months for 55 (96.5%) ECPR survivors, cognitive testing for 44 (77.2%) and neurologic examination for 47 (82.5%). At 12 months, 39 (70.9%) ECPR survivors had VABS-II scores ≥70. On cognitive testing, 24 (54.6%) had scores ≥70, and on neurologic examination, 28 (59.5%) had no/minimal to mild impairment. Cognitive and neurologic score distributions were similar between ECPR, later ECMO and no ECMO groups. Conclusions: Many ECPR survivors had favourable outcomes although impairments were common. ECPR survivors had similar outcomes to other survivors who were initially comatose post-arrest.